Diagnostic accuracy of shear wave elastography in companion animal soft tissue injury: a systematic review - Chin Yi Lin (2023)
An abstract of the research paper presented to the Faculty of Veterinary Medicine, Universiti Malaysia Kelantan, in partial requirement on the course DVT 55204 – Research Project Shear wave elastography (SWE) is a novel diagnostic modality to evaluate tissue stiffness in relation to the tissue’s molecular constitution and disease status. This imaging technique measures the propagation velocity of the shear wave in relation to the tissue’s stiffness – the stiffer the tissue, the faster the waves are. This systematic review is conducted to identify the diagnostic accuracy and peculiar organ sensitivities towards SWE while evaluating if this technique is feasible in small animal clinical settings. Thus, a total of 15,339 publications from 2010 to 2022 were extracted from three databases, Google Scholar, PubMed, and Science Direct using different search strategies. A total of 17 studies have met the eligibility criteria after sequential screenings according to the inclusion and exclusion criteria. 25 examinations across 17 studies, 36.0% of studies discussed SWE in the canine or feline liver, specifically hepatic fibrosis, followed by 12.0% that discussed pancreatic lesions. Other parenchymatous organs were also discussed, including the mammary gland, kidney, spleen, peripheral lymph nodes, pancreas, prostate, kidney, thyroid, salivary glands, and muscles. Until now, the liver remained the most studied organ for the diagnostic accuracy of SWE in small animal practice. SWE was proven to positively correlate with other diagnostic standards including strain elastography, FNA biopsy, and histopathological examination, and is expected to be used as an adjunct diagnostic method in detecting tissue stiffness and parenchymatous organ injury with increased accuracy. Keywords: Shear wave elastography, canine, feline, diagnostic accuracy, feasibility